2007
DOI: 10.1016/j.nuclcard.2007.06.114
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine versus regadenoson comparative evaluation in myocardial perfusion imaging: Results of the ADVANCE phase 3 multicenter international trial

Abstract: This phase 3 trial shows that regadenoson provides diagnostic information comparable to a standard adenosine infusion. There were no serious drug-related side effects, and regadenoson was better tolerated than adenosine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
289
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(311 citation statements)
references
References 40 publications
18
289
1
3
Order By: Relevance
“…Regadenoson, approved by the United States Food and Drug Administration in April 2008, is increasingly used as a stress agent of choice because of its ease of administration as a bolus, weight-unadjusted dose, fast onset and short duration of action, sufficient hyperemic response, and comparable efficacy to adenosine but with fewer side effects. 15,16 The safety of regadenoson in patients with liver failure has been addressed in 1 study, 17 but no previous study has described the predictive value of regadenoson in patients with liver failure. Studies with adenosine SPECT imaging in patients with ESLD have also been limited, and results have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Regadenoson, approved by the United States Food and Drug Administration in April 2008, is increasingly used as a stress agent of choice because of its ease of administration as a bolus, weight-unadjusted dose, fast onset and short duration of action, sufficient hyperemic response, and comparable efficacy to adenosine but with fewer side effects. 15,16 The safety of regadenoson in patients with liver failure has been addressed in 1 study, 17 but no previous study has described the predictive value of regadenoson in patients with liver failure. Studies with adenosine SPECT imaging in patients with ESLD have also been limited, and results have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Affected coronaries fail to dilate properly resulting in a coronary steal phenomenon, manifested as a non-homogenous increase in coronary blood flow, which is reflected in the non-homogeneous distribution of the radio-isotope that can be mapped using a gamma-camera. Adenosine and ATP, and more recently a selective A2AR agonist (Lexiscan [458]), have been used as pharmacologic stressors in this setting [746][747][748][749][750][751][752][753][754]. The use of adenosine-cardiac magnetic resonance imaging for the detection of CAD has been recommended recently [755][756][757].…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…9,10 The ADVANCE MPI Trials 11,12 are randomized multicenter phase 3 trials that demonstrated the noninferiority of regadenoson to adenosine in detecting reversible defects by comparing the strength of agreement between sequential adenosine-regadenoson and adenosine-adenosine images. The HR and BP were measured at baseline and at predetermined intervals extending to 45 minutes after the administration of adenosine or regadenoson.…”
mentioning
confidence: 99%